The Nymph and Additional Imaginal Description of Epeorus melli new combination from China (Ephemeroptera: Heptageniidae) - Zhou, Chang-Fa; Wang, Shi-Lei; Xie, Hui (Zootaxa, 2007)
The nymph plus additional imaginal characters of Epeorus melli (Ulmer) new combination are described and figured in detail. The nymphs have 2 cerci, gills 1–7 which do not form a closed disk ventrally, and abdominal terga with a median row of setae dorsally but without median tubercle. Originally described in the genus Thalerosphyrus, it is actually a member of the genus Epeorus.